Young, metal-enriched cores in early-type dwarf galaxies in the Virgo cluster based on colour gradients - Ulrich, Linda; Lisker, Thorsten; Janz, Joachim (Astronomy and astrophysics, 2017)
Early-type dwarf galaxies are not simply featureless, old objects, but were found to be much more diverse, hosting substructures and a variety of stellar population properties. To explore the stellar content of faint early-type galaxies, and to investigate in particular those with recent central star formation, we study colours and colour gradients within one effective radius in optical (g − r) and near-infrared (i − H) bands for 120 Virgo cluster early-type galaxies with − 19 mag < Mr < − 16 mag. Twelve galaxies turn out to have blue cores, when defined as g − r colour gradients larger than 0.10 mag/Reff, which represents the positive tail of the gradient distribution. For these galaxies, we find that they have the strongest age gradients, and that even outside the blue core, their mean stellar population is younger than the mean of ordinary faint early-type galaxies. The metallicity gradients of these blue-cored early-type dwarf galaxies are, however, in the range of most normal faint early-type galaxies, which we find to have non-zero gradients with higher central metallicity. The blue central regions are consistent with star formation activity within the last few 100 Myr. We discuss whether these galaxies could be explained by environmental quenching of star formation in the outer galaxy regions while the inner star formation activity continued.
Gesehen am 26.03.2018